2010
DOI: 10.1128/jvi.01979-09
|View full text |Cite
|
Sign up to set email alerts
|

NS1′ of Flaviviruses in the Japanese Encephalitis Virus Serogroup Is a Product of Ribosomal Frameshifting and Plays a Role in Viral Neuroinvasiveness

Abstract: Flavivirus NS1 is a nonstructural protein involved in virus replication and regulation of the innate immune response. Interestingly, a larger NS1-related protein, NS1, is often detected during infection with the members of the Japanese encephalitis virus serogroup of flaviviruses. However, how NS1 is made and what role it performs in the viral life cycle have not been determined. Here we provide experimental evidence that NS1 is the product of a ؊1 ribosomal frameshift event that occurs at a conserved slippery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
222
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(239 citation statements)
references
References 23 publications
16
222
1
Order By: Relevance
“…We also demonstrated that RNA sequence encompassing codon 30 in the NS2A gene was critical for the formation of pseudoknot interactions involved in the 21 ribosomal frameshifting, which leads to the synthesis of an extended NS1 protein product, NS1' (Firth & Atkins, 2009;Melian et al, 2010). The A30P mutation disrupted pseudoknot interactions and resulted in abrogation of NS1' production (Melian et al, 2010). Hence, the highly attenuated phenotype of the A30P mutant can be attributed to two factors: (i) lack of frameshifting/NS1' synthesis caused by changes in the RNA sequence/structure, and (ii) the effect of the A30P codon substitution on the properties of the NS2A protein.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We also demonstrated that RNA sequence encompassing codon 30 in the NS2A gene was critical for the formation of pseudoknot interactions involved in the 21 ribosomal frameshifting, which leads to the synthesis of an extended NS1 protein product, NS1' (Firth & Atkins, 2009;Melian et al, 2010). The A30P mutation disrupted pseudoknot interactions and resulted in abrogation of NS1' production (Melian et al, 2010). Hence, the highly attenuated phenotype of the A30P mutant can be attributed to two factors: (i) lack of frameshifting/NS1' synthesis caused by changes in the RNA sequence/structure, and (ii) the effect of the A30P codon substitution on the properties of the NS2A protein.…”
mentioning
confidence: 99%
“…Flavivirus NS proteins are known to be involved in RNA replication, virion formation, cleavage of viral polyprotein, induction of virus-specific membrane structures and regulation of innate immune response (Ashour et al, 2009;Lindenbach & Rice, 1997;Liu et al, 2005;Nestorowicz et al, 1994;Patkar & Kuhn, 2008;Rossi et al, 2007;Westaway et al, 2003;Wicker et al, 2006). In addition, encephalitic viruses from the JEV serogroup produce NS1', an extended version of NS1, which is the result of ribosomal frameshifting in the N-terminal region of the NS2A gene (Firth & Atkins, 2009;Melian et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For transfection, the 20 ml (, 20 mg) RNA transcript mix was used to electroporate 6610 6 Vero cells resuspended in 0.4 ml cold phosphate-buffered saline (PBS), pH 7.4, in 0.4 cm cuvettes with the GenePulser apparatus (Bio-Rad); the following settings were applied: 4 pulses of 0.29 kV and 25 mF at 4s intervals. After a 10 min recovery, cells were mixed with D-MEM supplemented with 2% FBS and incubated in a T-25 flask (5% CO 2 at 37uC) until a cytopathic effect (CPE) was observed (referred to as passage 0, P0).…”
Section: Rna Transcription and Transfectionmentioning
confidence: 99%
“…Genomic RNA codes for a single and long polyprotein which is coand post-translationally cleaved by cellular and viral proteases. There are three structural proteins (C, prM/M and E) followed by seven nonstructural (NS) proteins (NS1, NS2A, NS2B, NS3, NS4A, NS4B, NS5) [5], along with NS1', which results from a -1 ribosomal frameshift event [6]. Structural proteins provide the structural elements of viral particles, while nonstructural proteins play a role in viral replication, virion assembly, and evasion of host antiviral immune responses [7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%